A retrospective cohort study on the treatment outcomes and genotyping of isoniazid-resistant tuberculosis patients in Eastern China. (September 2022) - Li, Yishu; Shi, Jinyan; Song, Wenlei; Shao, Yan; Zhu, Limei; Chen, Cheng
Highlights: Adverse outcomes in the HR-TB group were more frequent than in the DS-TB group. The Beijing genotype was the dominant genotype for HR-TB. Standard first-line regimens were commonly prescribed for HR-TB. ABSTRACT: Objectives: Isoniazid resistance might be overlooked because of the priority of detection of rifampicin-resistant tuberculosis. It was urgent to reveal the current situation of isoniazid-resistant tuberculosis (HR-TB), including unfavorable outcomes and bacterial factors. Methods: A retrospective cohort study was undertaken including 120 patients with HR-TB and 193 patients with drug-sensitive tuberculosis (DS-TB). 24-loci MIRU-VNTR and Spoligotyping were adopted for genotyping. Results: We found 106 cases (88.3%) of HR-TB and 165 cases (85.5%) of DS-TB were treated with the first-line drugs. Meanwhile, 12 (10.0%) patients of the HR-TB group and 7 (3.63%) patients of the DS-TB group involved adverse treatment outcomes (χ 2  = 5.271, P  = 0.028). Seventy-eight DNA from HR Mycobacterium tuberculosis and 114 DNA from DS M. tuberculosis were available for MIRU-VNTR and Spoligotyping. The clustering rate was 17.9% (14/78) for HR-TB and 16.7% (19/114) for DS-TB, and reached no significant difference (χ 2  = 0.05, P  = 0.8171). The Beijing family strains accounted for 83.7% (65/78) of HR-TB and 80.0% (91/114) of DS-TB (χ 2  = 0.37, P  = 0.5407). The adverse treatment outcomes for HR-TB all occurred in patients infected with Beijing family strains (13.8%), but no difference was found between Beijing and non-Beijing genotypes ( P  = 0.342). Conclusion: Adverse outcomes were significantly more frequent in patients with HR-TB than in those with DS-TB, and most of the patients with HR-TB were receiving a standard first-line regimen. Although the clustering rate and Beijing genotype distribution amongst HR-TB and DS-TB showed no significant difference, the Beijing genotype was the dominant genotype and its proportion was slightly higher amongst HR-TB than amongst DS-TB.